Remote house calls [disease detector]. - Rovetta, A.
An innovative bio-robotic system DDX for neuropsychophysical health-condition detection is presented. The proposed fuzzy logic solution is portable without losing efficiency and accuracy in diagnosis and also provides the ability to transfer diagnoses through a remote communication interface in order to monitor the daily health of a patient. The system is an intelligent machine based on soft computing techniques, and its efficiency can be improved considering more patterns of examples for functions, calibration, or, moreover, by using self-learning techniques.
Keywords: Biomedical robotic system; Calibration; Fuzzy logic; Neuropsychophysical health-condition detection; Patient diagnosis; Self-learning.; Soft computing